THE APLICATION OF PROBLEM BASED LEARNING MODEL ON HEAT AND TEMPERATURE - Pintor Simamora; Victorya Rotua Estomihi Pardede (Jurnal Pendidikan Fisika, 2016)
This study aims to determine the effect of Problem Based Learning model to student learning outcomes on subject of Heat and Temperature. This research is quasi-experimental. Techniques that used to gain a sample is random-cluster-sampling technique that was chosen two classes as experimental and control classes. Instruments in the form of essays tests and observation sheets to measure affectivepsychomotor of students. Pretest data on both classes showed that both classes have the same ability. Then be given treatment which experimental class with Problem Based Learning and control class with Conventional Learning. From the t-test results there is effect of Problem Based Learning model to student learning outcomes.